NEW ASPECTS IN THE MATTER OF PROTECTION MEASURES FOR PEOPLE WITH INTELLECTUAL AND PSYCHOSOCIAL DISABILITIES - Izabela BRATILOVEANU (Challenges of the Knowledge Society)
In order to comply with the CCR dec. no. 601/2020, the Law no. 140/2022 on some protection measures for persons with intellectual and psychosocial disabilities and amending and completion of some normative acts was adopted. According to art. 26 of the Law, most of its provisions entered into force 90 days after the date of publication in the Official Gazette of Romania, i.e., on August 18, 2022, except for the provisions of article 20 paragraph (6) thesis III and of article 23, which entered into force 3 days after publication. The measure of placing under judicial interdiction has been replaced, the current study aiming to analyze the new legal instruments of support and protection that are addressed to these categories of vulnerable persons that were created by Law no. 140/2022. The adoption of this normative act, whose solutions we will present in this study, is welcome and long awaited because the lack of a legislative framework in this important matter starting with the date of the publication of the Constitutional Court Decision left open the way for the courts to issue divergent solutions in cases having as object the „judicial interdiction”. Within 3 years from the entry into force of Law no. 140/2022, the ex officio re-examination of the injunction measures by the courts is carried out, in the sense of ordering either their replacement with the protective measures provided for by the new regulation, or the lifting of the measure, and the fulfillment of the deadline does not remove the obligation of the courts to re-examines, further, ex officio, all the measures of placing under judicial interdiction.